Kepemimpinan untuk Masyarakat Sipil - Wibawa, Samodra (JKAP (Jurnal Kebijakan dan Administrasi Publik), 1996)
It is apparent that the middle class in Indonesia is experiencing change in all &mentions including the economic. social and political aspects. This change. ofcource. requires that there is a shift in the paradigm of the athninistration of-development which has a paternalistic pattern pointing toward an egalitarian and participative pattern. The desire for this shill can only be fulfilled by among others. a shift in leadership which is initiated by the public leaders themselves. 77rc mahor is ultimately lured to draw a conclusion that the application of carious leadership soles which air explored in this piece of work will Ivy much depend on the assumptions which are used when evamining the community as a whole. If the civil society in Indonesia is seen as one which will grow towards the social situation as it is intended to be shaped. then the choice of a participative type of leadership becomes inevitable.